DYNAMIC ANALYSIS AND OPTIMIZATION OF IMPACT MECHANISM FOR IMPACTING AND BREAKING ROCK ROADEADER - LI XiaoHuo; QIAN YaSen; JIAO Li; LI Yan; SHI ShangWei; WENG ZhengYang (Jixie qiangdu)
In order to improve the impact mechanism of the impacting and breaking rock roadheader dynamic characteristics under the cycle impact load,the first six natural frequency and mode shape as well as the displacement-frequency curves were obtained by using stress wave synthesis theory and finite element method in the paper,the modal and harmonic response of the mechanism were analyzed,the main deformation portion and main vibration direction and three axial weakest points of the mechanism were confirmed,structure size optimization of the rocker arm were adopted with multiple objective genetic algorithm,The maximum displacement response of the mechanism was reduced,and the dynamic characteristics of the mechanism were improved,which provides a method and basis for researching and improving the dynamic performance of the mechanism.